1996
DOI: 10.1021/bi952868l
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Specific Adenosine N3-Nitrogens for Efficient Cleavage by a Hammerhead Ribozyme

Abstract: Five modified hammerhead ribozyme/substrate complexes have been prepared in which individual adenosine N3-nitrogens have been excised and replaced with carbon. The modified complexes were chemically synthesized with the substitution of a single 3-deazzaadenosine (c3A) base analogue for residues A6, A9, A13, A14, or A15.1. Steady-state kinetic analyses indicate that the cleavage efficiencies, as measured by kcat/K(M), for the c3A6, c3A9, and c3A14 complexes were only marginally reduced (< or = 5-fold) relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 61 publications
2
22
0
2
Order By: Relevance
“…In the ground-state structure of the hammerhead, the A13 nucleotide forms a nonstandard G{A pair with G8 (Fig+ 1)+ Pairing occurs via three hydrogen bonds, involving the exocyclic amino group and the N7 atom of A13 (Pley et al+, 1994;Scott et al+, 1995) (Fig+ 9)+ Removal of the base from A13 essentially abolishes catalysis, reducing the cleavage rate by almost 10 6 -fold (Table 1) (Peracchi et al+, 1996)+ Addition of adenine to near its solubility limit (;3 mM) gives a modest rescue of ;30-fold (Peracchi et al+, 1996)+ A survey of rescue for A13X is reported in Table 4+ Strikingly, many of the purines tested rival the rescuing efficiency of adenine, the base originally removed+ Compounds containing an exocyclic amino group, such as adenine or 2-aminopurine, or a keto group, such as hypoxanthine, and purine, which lacks exocyclic groups, all show similar values of k rescue + These observations with base rescue mirror the small effects observed previously with hammerhead constructs containing purine, 1-deazaadenosine, 3-deazaadenosine, 7-deazaadenosine, or isoguanosine substituted at position 13 (Fu & McLaughlin, 1992a;Slim & Gait, 1992;Fu et al+, 1993;Seela et al+, 1993;Bevers et al+, 1996;Seela et al+, 1998)+ Finally, the nucleosides adenosine and guanosine are surprisingly efficient in rescue at position 13 relative to the poor rescue observed with nucleosides at other positions (Tables 2-4; Peracchi et al+, 1996), suggesting that a greater freedom of motion at position 13 minimizes steric clashes of the nucleoside and backbone sugars+ FIGURE 7. The effects of probing a redundant functional interaction via site-directed mutagenesis (A) or base rescue (B), described by free energy reaction profiles+ A: For the wild-type ribozyme, the interaction in question is present in both the ground state and in the transition state+ Removal of the interacting functional group of the base ( Ⅲ ) destabilizes the ground state and the transition state to the same extent because, in this model, the remaining redundant interactions are sufficient to maintain the local structure+ Thus, the experiment does not reveal whether the functional group removed is involved in an interaction in the transition state (k ϭ k9)+ B: A base rescue experiment probing the same interaction+ Removal of the interacting functional group of the base is deleterious to rescue (k rescue .…”
Section: Rescue At Position 13supporting
confidence: 62%
See 1 more Smart Citation
“…In the ground-state structure of the hammerhead, the A13 nucleotide forms a nonstandard G{A pair with G8 (Fig+ 1)+ Pairing occurs via three hydrogen bonds, involving the exocyclic amino group and the N7 atom of A13 (Pley et al+, 1994;Scott et al+, 1995) (Fig+ 9)+ Removal of the base from A13 essentially abolishes catalysis, reducing the cleavage rate by almost 10 6 -fold (Table 1) (Peracchi et al+, 1996)+ Addition of adenine to near its solubility limit (;3 mM) gives a modest rescue of ;30-fold (Peracchi et al+, 1996)+ A survey of rescue for A13X is reported in Table 4+ Strikingly, many of the purines tested rival the rescuing efficiency of adenine, the base originally removed+ Compounds containing an exocyclic amino group, such as adenine or 2-aminopurine, or a keto group, such as hypoxanthine, and purine, which lacks exocyclic groups, all show similar values of k rescue + These observations with base rescue mirror the small effects observed previously with hammerhead constructs containing purine, 1-deazaadenosine, 3-deazaadenosine, 7-deazaadenosine, or isoguanosine substituted at position 13 (Fu & McLaughlin, 1992a;Slim & Gait, 1992;Fu et al+, 1993;Seela et al+, 1993;Bevers et al+, 1996;Seela et al+, 1998)+ Finally, the nucleosides adenosine and guanosine are surprisingly efficient in rescue at position 13 relative to the poor rescue observed with nucleosides at other positions (Tables 2-4; Peracchi et al+, 1996), suggesting that a greater freedom of motion at position 13 minimizes steric clashes of the nucleoside and backbone sugars+ FIGURE 7. The effects of probing a redundant functional interaction via site-directed mutagenesis (A) or base rescue (B), described by free energy reaction profiles+ A: For the wild-type ribozyme, the interaction in question is present in both the ground state and in the transition state+ Removal of the interacting functional group of the base ( Ⅲ ) destabilizes the ground state and the transition state to the same extent because, in this model, the remaining redundant interactions are sufficient to maintain the local structure+ Thus, the experiment does not reveal whether the functional group removed is involved in an interaction in the transition state (k ϭ k9)+ B: A base rescue experiment probing the same interaction+ Removal of the interacting functional group of the base is deleterious to rescue (k rescue .…”
Section: Rescue At Position 13supporting
confidence: 62%
“…The three-dimensional structure of the hammerhead ribozyme shows that the adenine base at position 9 is involved in a nonstandard base pair with G12, and that this pair is stacked between a Watson-Crick base pair (G10+1{C11+1) and another nonstandard pair (G8{A13) (Fig+ 6;Pley et al+, 1994;Scott et al+, 1995)+ The A9{G12 pair involves three hydrogen bonds, two with the exocyclic amino group of the adenine and one with N7 of this base (Fig+ 6)+ We previously showed that removing the A9 base in the HH16 hammerhead core decreases catalysis by 2,000-fold (Peracchi et al+, 1996) (Table 1) and that exogenous addition of 3 mM adenine activates this abasic variant by 300-fold, to within 10-fold of the wild-type rate (Peracchi et al+, 1996)+ Table 3 summarizes the results from rescue experiments of A9X with 28 different bases+ Rescue was specific for purines compared to pyrimidines+ Furthermore, K rescue for adenine was ;30-fold higher than for purine itself, suggesting a functional interaction with the 6-amino group of the rescuing base+ In addition, methylation of the adenine ring at position 7 decreases k rescue by ;fivefold+ This is consistent with disruption of an interaction of N7 in the transition state, although a steric effect cannot be excluded+ Rescue by 3-methyladenine is similar to that by unmodified adenine, and rescue by 2-methyladenine is even better, suggesting that there are no functional interactions at positions 2 and 3 in the transition state of the wild-type ribozyme+ Previous sitespecific mutagenesis studies, in which A9 had been modified to 1-deazaadenine and 3-deazaadenine, suggested that N1 and N3 do not engage in a critical transition state interaction (Bevers et al+, 1996;Seela et al+, 1998)+ Overall, although the effects on base rescue from modifying the adenine functional groups are modest, the data above are consistent with A9 forming the same interactions in the transition state that are observed in the ground-state crystal structure, without the formation of new functional interactions+ Given the accumulating evidence for a substantial precatalytic rearrangement of the hammerhead core structure discussed above, it is important to map positions that do and do not take on additional transition state interactions+ Replacement of the A9 base by an unsubstituted phenyl ring (to give variant A9⌽, with ⌽ indicating the phenyl nucleotide derivative shown in Fig+ 2B) decreases catalysis by a modest 20-fold compared to the 2,000-fold deleterious effect from removal of the base (Table 1)+ Such effectiveness of the phenyl substitution FIGURE 6. Schematic representation of the hydrogen bonding interactions of the A9 base observed in the crystal structures of the hammerhead ribozyme (Pley et al+, 1994;Scott et al+, 1995Scott et al+, , 1996Murray et al+, 1998)+ relative to abasic substitution is observed at only three of the nine positions in the HH16 core at which both modifications were tested (Table 1)+ What is the role of the A9 base in hammerhead catalysis?…”
Section: Efficient Rescue By Adenine At Positionmentioning
confidence: 99%
“…It has been reported that the stability of base pairing and tertiary folding is reduced in the presence of organic solvents, particularly amide compounds that are known to substantially destabilize nucleic acid structures [31,44]. However, this destabilization effect seemed not to cause a disruption of interactions necessary for the formation of the active conformation, such as a network of hydrogen bonds [48], in the presence of 10 mM MgCl 2 . The correlation plot of Figure 1e suggests that the dielectric constant influences the turnover rate.…”
Section: Effects On the Hammerhead Ribozymementioning
confidence: 99%
“…However, 3-deazaadenosine substitution in the hammerhead ribozyme considerably reduces its catalytic efficiency, which indicates an important role for the N-3 nitrogen atom in the reaction (166). Similarly, when 3-deazaadenosine was substituted in the recognition sequence of EcoRV methylase, the enzymatic reaction was inhibited, thus implying a role for N-3 nitrogen in protein-DNA recognition (167).…”
Section: Purine Modificationsmentioning
confidence: 99%
“…Other analogs such as purine, isoguanine, 2,6-diaminopurine, 6-thioguanine, and hypoxanthine have been used as probes for the identification of purine nucleosides essential for protein-DNA interaction (167,(170)(171)(172) and RNA catalysis (166,(173)(174)(175) and to estimate the contribution of the hydrophobic interaction in duplex stability (176). A more detailed account of purine and pyrimidine nucleoside analogs and their utility in delineating biochemical mechanisms can be found elsewhere (177,178).…”
Section: Purine Modificationsmentioning
confidence: 99%